2011
DOI: 10.1007/s11064-011-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinione Inhibits β-Amyloid Aggregation and Protects Damage from β-Amyloid in SH-SY5Y Cells

Abstract: The deposition of amyloid β-protein (Aβ) fibrils into plaques within the brain parenchyma and along cerebral blood vessels is a hallmark of Alzheimer's disease (AD). Aβ42 oligomers and fibrils cause the breakdown of neural circuits, neuronal death and eventually dementia. Drugs that inhibit Aβ42 aggregation may be a novel direction in AD drug discovery. Cryptotanshinone (CTS), an active component of the medicinal herb Salvia miltiorrhiza, has been shown to improve learning and memory in several pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…This process is an imbalance between the systemic manifestations of RNS and ROS [12], [13]. Many neurodegenerative diseases have high levels of oxidative stress, especially those affected by ROS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is an imbalance between the systemic manifestations of RNS and ROS [12], [13]. Many neurodegenerative diseases have high levels of oxidative stress, especially those affected by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Cells (1×10 5 ) were incubated with 30 µM of Aβ peptides for 48 hours. Before conducting flow cytometry, the cells were treated with 10 µM of DCFH-DA for 30 minutes at 37°C, followed by washing with PBS [12], [13]. Data analyses were performed using program Kaluza software, version 1.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proapoptotic effect of Cryptotanshinone has partially been explained by sensitisation to TRAIL [15,17]. On the other hand, Cryptotanshinone has been shown to counteract apoptosis in some cell types [18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…16, 17 Cryptotanshinone (CTS), one of the major representative components isolated from the root of Salvia miltiorrhiza Bunge has been reported to have inhibitory effects on STAT3 activation. It was also reported to have other pharmacological effects including anticardiovascular diseases, 18 anti-inflammation, 19, 20 neuron protection 21 and antiproliferation of cancer cells. 22 We recently observed that CTS suppressed the proliferation of human MG cells T98G and U87 through inhibition of STAT3 signaling pathway.…”
mentioning
confidence: 99%